Three-dimensional computed tomography angiography and bronchography combined with three-dimensional printing for thoracoscopic pulmonary segmentectomy in stage IA non-small cell lung cancer - Hu, Wenbin (J Thorac Dis, 2021)
BACKGROUND: Compared with lobectomy, the anatomical structure of the lung segment is relatively complex and easy to occur variation, thus it increases the difficulty and risk of precise segmentectomy. The application of three-dimensional computed tomography bronchography and angiography (3D-CTBA) combined with a three-dimensional printing (3D printing) model can ensure the safety of operation and simplify the surgical procedure to a certain extent. We aimed to estimate the value of 3D-CTBA and 3D printing in thoracoscopic precise pulmonary segmentectomy. METHODS: We retrospectively reviewed the clinical data of 65 patients who underwent anatomical segmentectomy at the Affiliated Hospital of Shaoxing University from January 2019 to August 2020. The patients were divided into two groups: a 3D-CTBA combined with 3D printing group (30 patients) and a general group (35 patients). The perioperative data of the two groups were compared. RESULTS: Compared with the general segmentectomy group at the same period in our center, the surgery time of the group guided by 3D-CTBA and 3D printing was significantly shorter. Intraoperative blood loss in the 3D-CTBA and 3D printing group was also apparently lower than in the general group. Hospital stay and postoperative chest tube duration showed no significant differences between the two groups, and neither did postoperative complications such as pneumonia, hemoptysis, arrhythmia, and pulmonary air leakage. CONCLUSIONS: 3D-CTBA combined with 3D printing clearly identifies the precise pulmonary segmental structures, avoids intraoperative accidental injury, reduces intraoperative blood loss, shortens the operation time and improves the safety of thoracoscopic pulmonary segmentectomy in stage IA non-small cell lung cancer (NSCLC).